2004
DOI: 10.1515/hf.2004.002
|View full text |Cite
|
Sign up to set email alerts
|

Cationic effect in high concentration alcohol organosolv pulping: The next generation biorefinery

Abstract: Catalyst employment in cooking liquor of 80% aqueous methanol is required for fiber liberation at high yield (50%) and has a remarkable impact on pulp production capability in the alcohol organosolv pulping of spruce wood. In alcohol solution without a suitable catalyst, the softwood fibers cannot be effectively liberated from the wood matrix. The effectiveness of the catalysts tested in this research varied widely. Divalent metal ions were found to be very effective, whereas monovalent cations were incapable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…HCl was used as alternative acid, since it has been reported to be effective in methanol, ethanol, and acetic acid‐based (Acetosolv) organosolv pulping 3. Finally, MgCl 2 was selected as a non‐acid catalyst based on work by Yawalata and Paszner 22, 23. They reported MgCl 2 to be the optimum catalyst in an extensive study on the catalytic effect of various salts on methanol‐based organosolv pulping of spruce wood for paper applications (neutral alkali earth metal (NAEM) process) 22, 23.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCl was used as alternative acid, since it has been reported to be effective in methanol, ethanol, and acetic acid‐based (Acetosolv) organosolv pulping 3. Finally, MgCl 2 was selected as a non‐acid catalyst based on work by Yawalata and Paszner 22, 23. They reported MgCl 2 to be the optimum catalyst in an extensive study on the catalytic effect of various salts on methanol‐based organosolv pulping of spruce wood for paper applications (neutral alkali earth metal (NAEM) process) 22, 23.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, these studies are mainly limited to organosolv treatment of softwoods. For example, Yawalata and Paszner studied the effect of different chlorine salts,23 magnesium salts,22 and acid catalysts22 on methanol‐based organosolv pulping of spruce. They obtained optimum results with MgCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium chloride is another important inorganic salt used in the ethanol organosolv pretreatment. Previous studies have shown that organosolv pulping using magnesium chloride as a catalyst resulted in comparable delignification and partial preservation of hemicellulose when compared with that using sulfuric acid as a catalyst (Yawalata & Paszner, , ). Huijgen et al () found that ethanol pretreatment for willow wood using magnesium chloride could yield similar enzymatic glucose yields of about 85% to the acid catalysts, while retaining more xylan in the pulp.…”
Section: Ethanol Organosolv Pretreatment and Enzymatic Hydrolysismentioning
confidence: 99%
“…A sodium carbonate solution of a concentration 65 to 120 g/L as Na 2 O at a liquor to wood ratio of 1.2-2.5 was used. Yawalata and Paszner [40] disclosed a solvent pulping method using aqueous solution of a lower aliphatic alcohol in a plurality of batch extraction vessels at a temperature between 160 to 220℃. A multi-stage extraction was used.…”
Section: -1-4 Corrosion[8]mentioning
confidence: 99%